2018
DOI: 10.1002/ijfe.1655
|View full text |Cite
|
Sign up to set email alerts
|

The determinants of profitability of Indian commercial banks: A panel data approach

Abstract: The current study examines the determinants of profitability of Indian commercial banks. The analysis is conducted over a period of 10 years in which the Indian banking sector has gone under different changes such as demonetization and issues related to banking sector sustainability and banking sector frauds. The analysis is based on balanced panel data over a period ranging from 2008 to 2017 for 69 commercial Indian banks. Profitability of Indian banks is measured by two proxies, namely, return on assets (ROA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

23
184
5
19

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 169 publications
(231 citation statements)
references
References 37 publications
(226 reference statements)
23
184
5
19
Order By: Relevance
“…As a result the banking sector in Sudan is insulated from the effect of international currency movements and its exposure to currency risk that may create unpredictable profits and losses is minimal. According to Almaqtari et al (2018), extent of deterioration of local currency as compared to other foreign currencies could be a reason for contradicting study results. The persistent worsening of the Sudanese Pound against the US dollar leads to a continuous devaluation of the national currency and changing, unstable fiscal and financial policies.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…As a result the banking sector in Sudan is insulated from the effect of international currency movements and its exposure to currency risk that may create unpredictable profits and losses is minimal. According to Almaqtari et al (2018), extent of deterioration of local currency as compared to other foreign currencies could be a reason for contradicting study results. The persistent worsening of the Sudanese Pound against the US dollar leads to a continuous devaluation of the national currency and changing, unstable fiscal and financial policies.…”
Section: Discussionmentioning
confidence: 82%
“…As stated by Kemisola et al (2016), the effect of exchange rate fluctuation on banks performance is materially affected by the specific measure used to judge the bank performance. According to Almaqtari et al (2018), extent of deterioration of local currency as compared to other foreign currencies may be a reason. Razi et al (2012) noted that magnitude of foreign direct investment may affect the extent and direction of association between exchange rare and bank profitability.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Dietrich and Wanzenried (2011) argued that well-capitalized banks are safe, remain profitable, and can become resilient, even during economic difficulties, and rely less on external funding. Almaqtari et al (2019) recently reported that by increasing their equity, the banks can absorb the negative results of a higher volume of non-performing loans arising as a result of excessive lending during economic boom periods. They further suggested that a high amount of regulatory capital indicates creditworthiness, which help reduces the cost of borrowing.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Along with the banks' specific factors, the researcher has also taken the macroeconomic factor to analyze its impact on the profitability such as; demonetization (Almaqtari et al 2018); inflation rate, oil price, market capitalization and rate of GDP rate, (Robin et al 2018); (Chowdhury & Rasid. 2017); competitive market and economy growth (Petria et al 2015); the rate of interest and rate of tax (Dietrich & Wanzenried, 2011); Inflation Rate and Financial Crisis, (Bouzgarrou et al 2017); GDP and Inflation, (Tan, 2016); political factors, (Yahya et al 2017) inflation and unemployment (Singh & Sharma 2016).…”
Section: Review Of Literaturementioning
confidence: 99%